Pendampingan Manajemen Kewirausahaan Melalui Pembuatan Eco Enzim dan Sabun Herbal Ramah Lingkungan dengan Memanfaatkan Limbah Rumah Tangga - Rohaeti, Eli; Rohmawati, Dini; Priastomo, Yoga; Afikah, Adilah; Sasmi, Weni Tri; Goni, Nur Abdul; Joronavalona, Rasamimanana; Dianti, Sekar Paramitha Rizqy (Yogyakarta State University, 2025)
The urgency of the Community Service Activities (PPM) that will be conducted is in accordance with the challenges faced by partners in the development of professional human resources for Advanced Indonesia. Specifically, family welfare requires further development through the provision of skills to women who are economically unproductive. The entrepreneurial spirit of women in the city of Yogyakarta, particularly mothers in Kampung Kuncen RT 21 RW 05, Pakuncen Village, Wirobrajan District, Yogyakarta City, is still relatively low. They require training to achieve independence, particularly in the field of green economy, in order to establish prosperous families by prioritizing environmental sustainability. The issue of domestic waste, which is the leftover vegetables and fruits produced by households, is also urgent. This waste is being disposed of in landfills or residential areas, which will contaminate the surrounding environment. Additionally, Yogyakarta is presently experiencing a waste disposal emergency. In reality, household waste, including unspent vegetables and fruits, can be repurposed as eco enzyme materials. These materials can be employed as air fresheners, cleansing agents, and as supplementary ingredients in the production of herbal soap. Furthermore, soap can be produced from cooking oil residue. The urgency of Community Service activities, particularly the issue of managing household waste (environmental aspect) and the issue of enhancing the abilities of women in assisting the family economy (economic aspect). Mentoring activities for the production of botanical soap and eco enzymes are proposed as a solution to these issues. The objective of the PPM activities is to enhance the comprehension and capabilities of women in the field of entrepreneurship by providing them with independence training through mentoring in the production of environmentally friendly herbal soap. This soap is made by utilizing used cooking oil as the primary ingredient and fruit and vegetable waste as raw materials for the production of eco enzymes, which are used as soap additives. PPM activities are intended to enhance Key Performance Indicator (KPI) 3 UNY, which refers to lecturers who engage in activities outside of the classroom. Furthermore, four students who are participating in this PPM activity have expertise in the preparation and management of a PPM activity. This will enhance the achievement of KPI 7, which is a collaborative and participatory class.